Revisión sistemática del uso terapéutico de células madre mesenquimales en enfermedades musculoesqueléticas o neurodegenerativas en caninos - Cueva Recalde, Pedro José (2019)
In recent years there has been an increase in the presentation of cases in canines of musculoskeletal or neurodegenerative diseases, which leads to an impairment in the quality of life of the patient, who constantly manifest pain or have diminished motor skills, for this reason conducted a systematic review of the therapeutic use of mesenchymal stem cells (MSCs) in musculoskeletal and neurodegenerative diseases in studies conducted between 2008 and 2018 in English and Spanish in three web search engines such as Pub Med, Cochrane Plus Library and Science Direct , within which for the systematized search Mesh terms and boléanos markers were used to extend the search range and not lose information during the search stage. It is worth mentioning that for the realization of this systematic review, the PRISMA method checklist and the flow diagram were always used to complete all the stages contemplated by this methodology. At the same time, eligibility and exclusion criteria were included, in order to better define the search for the desired articles during the screening stage; being one of the main criteria of exclusion those articles in which the dogs have been evaluated as research models for diseases in humans. The data obtained were evaluated by Fisher's exact test, which showed that there is no significant relationship (p 0.5) between the origin of the MSCs and the type of disease evaluated. In conclusion, it was determined that the main stem cells used for the treatment of these pathologies are mesenchymal stem cells of adipose tissue (Ad MSCs) and mesenchymal stem cells of bone marrow (BM MSCs) that provide a significant improvement after application decreasing the sensation of pain.